Acute and subacute clinical markers after sport-related concussion in rugby union players - Russo, M. J.; Salvat, F.; Kañevsky, A.; Allegri, R. F.; Sevlever, G. (Journal of Science and Medicine in Sport, 2023)
Objectives The purpose of this study was to investigate the relationship between on-field post-concussion symptoms reported by athletes, on-field neurological signs reported by a trainer or physician, and/or post-concussion symptoms 72h after brain injury in male rugby players.